Bevacizumab has bidirectional regulatory effects on the secretion of basic fibroblast growth factor in glioma cells. (May 2020) - Wei, Pei; Zhang, Zhainan; Lin, Mao; Zhou, Bin; Wang, Zhiyong
Highlights: Bevacizumab has bidirectional regulatory effects on the secretion of bFGF. Moderate VEGF neutralization reduced bFGF production in glioma cells. VEGF overblocking enhanced bFGF secretion in glioma cells. Abstract: Previous studies suggest that upregulated basic fibroblast growth factor (bFGF) plays a key role in the resistance to anti-vascular endothelial growth factor (VEGF) therapy in glioma. This study reported that anti-VEGF treatment regulated bFGF secretion in a double-edged manner. That is, moderate VEGF neutralization reduced bFGF production, whereas VEGF overblocking enhanced bFGF secretion in glioma cells. Our data provide a new perspective on the treatment of glioma with anti-VEGF, and the underlying mechanism is worthy of further study.